The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.3758/bf03193224
|View full text |Cite
|
Sign up to set email alerts
|

Bilingualism affects picture naming but not picture classification

Abstract: Bilinguals named pictures in their dominant language more slowly (and with more errors) than did monolinguals. In contrast, bilinguals named the same pictures as quickly as did monolinguals on the fifth presentation (in Experiment 2) and classified them (as human made or natural) as quickly and accurately as did monolinguals (in Experiment 1). In addition, bilinguals retrieved English picture names more quickly if they knew the name in both Spanish and English (on the basis of a translation test that bilingual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
360
4
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 417 publications
(415 citation statements)
references
References 50 publications
43
360
4
8
Order By: Relevance
“…By virtue of using each language only part of the time, bilinguals have used word forms particular to each language relatively less frequently than monolinguals -i.e., bilingualism entails a frequency-lag (Gollan & Silverberg, 2001;Gollan et al, 2002;Gollan et al, 2005;Gollan, Montoya, Cera, & Sandoval, 2008;Sandoval, Gollan, Ferreira, & Salmon, 2010; for similar ideas see Ivanova & Costa, 2008;Lehtonen, & Laine, 2003;Mägiste, 1979;Nicoladis, Palmer, & Marentette, 2007;Pearson et al, 1997;Ransdell & Fischler, 1987). Supporting this account, the bilingual disadvantage is especially large for retrieval of low-frequency words, whereas little or no bilingual disadvantage is found for production of high-frequency words.…”
mentioning
confidence: 62%
“…By virtue of using each language only part of the time, bilinguals have used word forms particular to each language relatively less frequently than monolinguals -i.e., bilingualism entails a frequency-lag (Gollan & Silverberg, 2001;Gollan et al, 2002;Gollan et al, 2005;Gollan, Montoya, Cera, & Sandoval, 2008;Sandoval, Gollan, Ferreira, & Salmon, 2010; for similar ideas see Ivanova & Costa, 2008;Lehtonen, & Laine, 2003;Mägiste, 1979;Nicoladis, Palmer, & Marentette, 2007;Pearson et al, 1997;Ransdell & Fischler, 1987). Supporting this account, the bilingual disadvantage is especially large for retrieval of low-frequency words, whereas little or no bilingual disadvantage is found for production of high-frequency words.…”
mentioning
confidence: 62%
“…Further evidence for delayed lexical access in bilinguals stems from studies using picture naming tasks both in L1 and L2 (Gollan et al, 2008, see Hanulová et al, 2011. These studies consistently report a bilingual disadvantage for naming, with proficient bilingual participants naming pictures significantly more slowly in their non dominant language (either L1 or L2 Gollan et al, 2005) as compared to monolinguals. In one study, slower naming has been demonstrated even for the first/dominant language of the bilingual speakers when compared with monolingual speakers (Ivanova & Costa, 2008).…”
Section: Discussionmentioning
confidence: 91%
“…Repetition priming effects tend to be smaller for picture classification than for picture naming (Durso & Johnson, 1979;Gabrieli et al, 1999;Gollan et al, 2005). Previous research has shown that semantic classification of pictures facilitates later picture naming (e.g., Carroll et al, 1985) and that picture naming facilitates later semantic classification (Vaidya et al, 1998).…”
Section: Methodsmentioning
confidence: 94%